THE INFLUENCE OF SOCIAL MEDIA ON RUNNING OUTFIT PURCHASING DECISIONS WITH FEAR OF MISSING OUT (FOMO) AS A MEDIATING VARIABLE - Indah Dwi Lestari; Rahmawati; Heni Rahayu Rahmawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study investigates the influence of social media on purchasing decisions for running outfits, with Fear of Missing Out (FOMO) as a mediating variable, among running community members in Sangatta, East Kutai Regency. The rapid advancement of digital technology has transformed consumer behavior, particularly through intensive use of social media platforms such as Instagram, TikTok, and Facebook, which serve as primary channels for product information and marketing promotion. In the context of running sports, social media not only shapes consumer preferences but also triggers the psychological phenomenon of FOMO the anxiety of being left behind in terms of trends and community experiences which may further drive purchasing behavior. This research employs a quantitative approach with purposive sampling. Data were collected through structured questionnaires distributed to one hundred and thirty active running outfit consumers aged eighteen to thirty-five years residing in Sangatta. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software, grounded in the Stimulus-Organism-Response (SOR) theoretical framework. The results confirm all four hypotheses. Social media has a positive and significant direct effect on purchasing decisions. Social media also positively and significantly influences the level of FOMO experienced by consumers. FOMO, in turn, has a positive and significant effect on purchasing decisions and emerges as the most dominant predictor in the model. Finally, FOMO significantly mediates the relationship between social media and purchasing decisions, indicating that social media influences purchasing behavior not only directly but also through the psychological mechanism of FOMO. These findings contribute to the digital marketing literature in developing regions of Eastern Indonesia and provide practical insights for sportswear businesses in leveraging social media content strategies effectively.